2012
DOI: 10.1002/etc.2042
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bisphenol A on growth and nitrogen nutrition of roots of soybean seedlings

Abstract: Abstract-Bisphenol A (BPA) is an environmental endocrine disruptor that seriously threatens ecological systems. Plants are the primary producers in ecological systems, but little information is available concerning the toxic effect of BPA on plants. In the present study, the effects of BPA on the growth and nitrogen nutrition of roots of soybean seedlings were investigated by using a root automatic scan apparatus and biochemical methods. It was found that when soybean seedlings were treated with 1.5 mg/L BPA, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 38 publications
1
28
0
Order By: Relevance
“…All rights reserved (length, fresh/dry weight, surface area, volume and activity of roots) [13] of plants. Moreover, the mechanisms of BPA action on plants have been primarily reported from nitrogen nutrient, photosynthesis [12] and membrane lipid peroxidation [14].…”
Section: Acc E P Ted P R E P R I Ntmentioning
confidence: 99%
“…All rights reserved (length, fresh/dry weight, surface area, volume and activity of roots) [13] of plants. Moreover, the mechanisms of BPA action on plants have been primarily reported from nitrogen nutrient, photosynthesis [12] and membrane lipid peroxidation [14].…”
Section: Acc E P Ted P R E P R I Ntmentioning
confidence: 99%
“…Therefore, nitrate assimilation in the soybean seedling roots that were treated with low‐concentration BPA was unchanged, whereas the single treatment with low‐concentration BPA promoted nitrate uptake (Figure A) . In this treatment, the improvement in soybean seedling root growth might be a result of the enhanced ammonia assimilation .…”
Section: Discussionmentioning
confidence: 94%
“…The combined treatment with the low‐concentration Cd and the high‐concentration BPA acts via similar mechanisms in plant cells as does the combined treatment with the high‐concentration Cd and the low‐concentration BPA (Table ). The combined treatment with the high‐concentration BPA and the high‐concentration Cd could synchronously inhibit the nitrate uptake and increase the ammonium accumulation and structural destruction of nitrate reductase and nitrite reductase, thereby decreasing the activities of nitrate reductase and nitrite reductase and, consequently, the inhibition of nitrate assimilation in soybean seedling roots (Figure ). Ultimately, soybean seedling root growth was inhibited (Table ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…), durum wheat and lettuce (Lactuca sativa L.) seedlings, moreover, root symptoms, including browning and the formation of jelly-like films, were also observed [12]. Some studies have demonstrated that treatment with 1.5 mg L -1 BPA promotes nitrogen assimilation in soybean (Glycine max L.) seedling roots [17,18] and…”
Section: Introductionmentioning
confidence: 94%